Manual praktek mengelola hutan dan lahan: suatu kombinasi pengetahuan tradisional masyarakat Dayak Kenyah dengan ilmu-ilmu kehutanan dan pertanian - Suhardiman, A.; Hidayat, A.; Applegate, G.; Colfer, C.J.P. (Center for International Forestry Research, 2002)
This simple manual is intended for general guidelines on traditional methods in managing natural resources. It is based on the indigenous/traditional knowledge of people of Dayak Kenyah Uma' Jalan society, East Kutai, Kalimantan, Indonesia. Local traditional knowledge is one of the important components to utilise and conserve the natural resources. This manual shows how to prepare the land for planting food crops, community forest management procedures and fire prevention.